Kinetics and Mechanism of the Reaction between Chromium(III) and 2,3-Dihydroxybenzoic Acid in Weak Acidic Aqueous Solutions - Athinoula L. Petrou; Vladimiros Thoma; Konstantinos Tampouris (Bioinorganic Chemistry and Applications)
The reaction between chromium(III) and 2,3-dihydroxybenzoic acid (2,3-DHBA) takes place in at least three stages, involving various intermediates. The ligand (2,3-DHBA)-to-chromium(III) ratio in the final product of the reaction is 1 : 1. The first stage is suggested to be the reaction of [Cr(H2O)5(OH)]2+ with the ligand in weak acidic aqueous solutions that follows an Id mechanism. The second and third stages do not depend on the concentrations of chromium(III), and their activation parameters are ΔH≠=61.2±3.1 kJmol−1, ΔS≠=−91.1±11.0 JK−1mol−1, ΔH≠=124.5±8.7 kJmol−1, and ΔS≠=95.1±29.0 JK−1mol−1. These two stages are proposed to proceed via associative mechanisms. The positive value of ΔS≠ can be explained by the opening of a four-membered ring (positive entropy change) and the breaking of a hydrogen bond (positive entropy change) at the associative step of the replacement of the carboxyl group by the hydroxyl group at the chromium(III) center (negative entropy change in associative mechanisms). The reactions are accompanied by proton release, as shown by the pH decrease.